Desert Puma : Evolutionary Ecology and Conservation of an Enduring Carnivore - Logan, Kenneth A. and Sweanor, Linda L. (Washington, DC Island Press, 2001)
Annotation Scientists and conservationists are beginning to understand the importance of top carnivores to the health and integrity of fully functioning ecosystems. As burgeoning human populations continue to impinge on natural landscapes, the need for understanding carnivore populations and how we affect them is becoming increasingly acute. Desert Pumarepresents one of the most detailed assessments ever produced of the biology and ecology of a top carnivore.
Include Index, References,Appendix And Colour Illustration
Keywords: New Mexico -- Desert animals -- Puma